محددات الربحية في البنوك التجارية دراسة حالة البنوك المدرجة في بورصة الدار البيضاء للفترة 2006 - 2019 (Journal of Economics and Management Research, 2020)
يهدف هذا البحث إلى دراسة محددات الربحية في البنوك المغربية المدرجة في بورصة الدار البيضاء، وذلك باستخدام نموذج الانحدار الذاتي VAR لعينة مكونة من (06) بنوك خلال الفترة (2006-2019). أظهرت النتائج وجود تأثير إيجابي لكل من معدل كفاية رأس المال ونسبة السيولة وحجم البنك على مؤشر الربحية، كما توصلت الدراسة إلى أن التسيير غير المحكم للنفقات يؤثر سلبا على ربحية البنوك التجارية. This research aims to study the determinants of profitability in the Moroccan banks listed on the Casablanca Stock Exchange, using a VAR self-regression model for a sample of (06) banks during the period (2006-2019). The results showed a positive impact of the capital adequacy ratio, the liquidity ratio, and the size of the bank on the profitability index. The study also concluded that the loose management of expenditures negatively affects the profitability of commercial banks.